Tunisia : Request for a Stand-By Arrangement: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2013)
Tunisia's macroeconomic situation has recovered from the post-revolution trough, but fiscal and external buffers have been eroded. Prudent management of monetary policy is crucial for short-term macroeconomic stabilization goals and to build external buffers. The challenges arise from social and economic disparities and high youth unemployment. The economic reform agenda appropriately aims at addressing these challenges through short-term stabilization goals while laying the foundations for supporting growth. Executive Directors commend the government's commitment to maintaining an appropriate fiscal stance while making space for critical spending priorities and repayments of arrears.